Road cycle TT performance: Relationship to the power-duration model and association with FTP - Morgan, P. T.; Black, M. I.; Bailey, S. J.; Jones, A. M.; Vanhatalo, A. (Journal of Sports Sciences, 2019)
Purpose: To determine the accuracy of critical power (CP) and W' (the curvature constant of the power-duration relationship) derived from self-paced time-trial (TT) prediction trials using mobile power meters to predict 16.1-km road cycling TT performance. This study also aimed to assess the agreement between functional threshold power (FTP) and CP.